2017
DOI: 10.1002/2017jf004231
|View full text |Cite
|
Sign up to set email alerts
|

Terrain controls on the occurrence of coastal retrogressive thaw slumps along the Yukon Coast, Canada

Abstract: Retrogressive thaw slumps (RTSs) are among the most active landforms in the Arctic; their number has increased significantly over the past decades. While processes initiating discrete RTSs are well identified, the major terrain controls on the development of coastal RTSs at a regional scale are not yet defined. Our research reveals the main geomorphic factors that determine the development of RTSs along a 238 km segment of the Yukon Coast, Canada. We (1) show the current extent of RTSs, (2) ascertain the facto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
80
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 73 publications
(85 citation statements)
references
References 52 publications
(126 reference statements)
3
80
1
1
Order By: Relevance
“…This prevents the development of thermo-erosional niches and consequently the rapid erosion by block collapse that is an important component at other Arctic riverbank and coastal cliff systems [11,14,17]. Given that the cliff top is decoupled from the thermo-erosional processes of the Lena River, its erosion likely results from atmospheric forcing and depends on the local sediment and ground ice properties [55], as well as regional climatic conditions [4]. This link explains the relatively gradual thermo-denudation at the cliff top.…”
Section: Intra-annual Dynamics Of Cliff-top Erosionmentioning
confidence: 99%
“…This prevents the development of thermo-erosional niches and consequently the rapid erosion by block collapse that is an important component at other Arctic riverbank and coastal cliff systems [11,14,17]. Given that the cliff top is decoupled from the thermo-erosional processes of the Lena River, its erosion likely results from atmospheric forcing and depends on the local sediment and ground ice properties [55], as well as regional climatic conditions [4]. This link explains the relatively gradual thermo-denudation at the cliff top.…”
Section: Intra-annual Dynamics Of Cliff-top Erosionmentioning
confidence: 99%
“…The size of the observed RTSs is one reason behind such differences: most of the RTSs examined in the above studies are classified as mega slumps (> 0.5 ha). RTSs along the Yukon coast are small, with an average size of 0.2 ha (Ramage et al, 2017). Furthermore, our estimates do not 25 include all of the material eroded by the RTSs; they only represent the amount of material released to the nearshore zone through slumping.…”
Section: Eroded Materials From Rtssmentioning
confidence: 99%
“…Lantuit and Pollard (2008) showed that the number of RTSs on Herschel 15 Island increased by 61% between 1952 and 2000. RTSs develop following changes that affect geomorphic settings (Ramage et al, 2017;Kokelj et al, 2017) and are induced by climatic conditions -such as increased air temperature (Lacelle et al, 2010), precipitation events (Kokelj et al, 2015;Lacelle et al, 2010) and storm events (Lantuit et al, 2012a;Lantuit and Pollard, 2008;Dallimore et al, 1996). Many RTSs that were stable or stabilized between 1952 and 1972 re-activated between 1972 and 2011.…”
Section: Acceleration Of Slump Activity 10mentioning
confidence: 99%
See 2 more Smart Citations